Strategies for preventing terrorism - Bjørgo, Tore (Palgrave Macmillan, 2013)
This innovative new book aims to put society's fight against terrorism into a comprehensive crime prevention perspective with a clear, understandable theoretical foundation, developing a general model for the prevention of crime which is, in this book, applied to terrorism